2022
DOI: 10.1099/jgv.0.001735
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 variants of concern alpha, beta, gamma and delta have extended ACE2 receptor host ranges

Abstract: Following the emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in PR China in late 2019 a number of variants have emerged, with two of these – alpha and delta – subsequently growing to global prevalence. One characteristic of these variants are changes within the spike protein, in particular the receptor-binding domain (RBD). From a public health perspective, these changes have important implications for increased transmissibility and immune escape; however, their presence could also m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Since our test allows to detect distinct cellular immune responses even 10 months after SARS‐CoV‐2 infection, with an even stronger IL‐2 release compared with the steadily decreasing anti‐S and anti‐N antibody levels, the WB test will be useful for the long‐term follow‐up of the COVID‐19 status. Moreover, this test may also be used for various farm animals such as ferrets or also ordinary hamsters, which were in the focus of recent attention, 50 , 51 as reservoir for infections and mutations and some countries even ordered the culling of those animals ( https://www.bbc.com/news/world‐europe‐54818615 , https://www.nature.com/articles/d41586‐021‐00531‐z ).…”
Section: Discussionmentioning
confidence: 99%
“…Since our test allows to detect distinct cellular immune responses even 10 months after SARS‐CoV‐2 infection, with an even stronger IL‐2 release compared with the steadily decreasing anti‐S and anti‐N antibody levels, the WB test will be useful for the long‐term follow‐up of the COVID‐19 status. Moreover, this test may also be used for various farm animals such as ferrets or also ordinary hamsters, which were in the focus of recent attention, 50 , 51 as reservoir for infections and mutations and some countries even ordered the culling of those animals ( https://www.bbc.com/news/world‐europe‐54818615 , https://www.nature.com/articles/d41586‐021‐00531‐z ).…”
Section: Discussionmentioning
confidence: 99%
“…Biologically, the apparent success of ACE2-based models in predicting sarbecovirus host range cannot be interpreted as evidence for a disproportionate mechanistic influence of ACE2 variation in restricting host range. While there is experimental evidence suggesting that variation in ACE2 alone can block infection (e.g., Guo et al, 2020 ; Thakur et al, 2022 ), how widely alleles conferring complete resistance occur in nature (particularly in species with no history of sarbecovirus exposure) remains unclear. Indeed, our data show that a broad diversity of ACE2 variation is permissive for infection, so such examples, though biologically verified, may be extremes that do not generalise across taxa.…”
Section: Discussionmentioning
confidence: 99%
“…We were also unable to incorporate polymorphism in ACE2 sequences or suspected variation in susceptibility below the species level, which has been reported in some rhinolophid bats ( Guo et al, 2020 ), since these fine-scale data were unavailable for most species. SARS-CoV-2 is also continuously evolving and this evolution may ultimately alter host range in ways that cannot be predicted by current models ( Thakur et al, 2022 ), which are necessarily based on infections reported with earlier strains. While previous approaches were not explicitly designed for non-SARS-CoV-2 sarbecoviruses, our results suggest the inclusion of additional sarbecoviruses did not adversely impact model performance ( Figure 2—figure supplement 3 , Figure 2—figure supplement 4 , Figure 4—figure supplement 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…This variant presents 10 main mutations in the spike protein: T19R, (G142D*), 156del, 157del, R158G, L452R, T478K, D614G, P681R, D950N [ 105 , 106 ]. Overall, the mutations presented by Delta and the previous variants (Alpha, Beta, and Gamma) show an enhanced adaptation to human ACE2, being also able to broaden their host ranges in comparison to the original SARS-CoV-2 [ 107 ].…”
Section: Main Sars-cov-2 Variantsmentioning
confidence: 99%